2019
DOI: 10.1002/pat.4679
|View full text |Cite
|
Sign up to set email alerts
|

Alginate hydrogels incorporating neomycin or propolis as potential dressings for diabetic ulcers: Structure, swelling, and antimicrobial barrier properties

Abstract: Alginate hydrogels have many attractive characteristics for potential use as wound dressing materials. However, they are not considered to possess any intrinsic activity against microbial infection, often present in neuropathic wounds. To overcome this, the effect of incorporating neomycin or propolis in alginate hydrogels was investigated, both by direct blending alone and also by further addition of loaded alginate microparticles prepared by the extrusion dripping method. The morphological, microstructural, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 60 publications
(133 reference statements)
0
8
0
Order By: Relevance
“…A much less abundant proportion of particles was detected in the range between 10-300 μm, indicating that shorter chains were less prevalent in the starting polymeric blend. Independent of the multimodality obtained, the dominant particle size ranges have been reported to be well suited for drug delivery and encapsulation purposes [ 103 ]. No apparent concentration-dependent trend is observed, but the freshly prepared formulations exhibited similar behavior.…”
Section: Resultsmentioning
confidence: 99%
“…A much less abundant proportion of particles was detected in the range between 10-300 μm, indicating that shorter chains were less prevalent in the starting polymeric blend. Independent of the multimodality obtained, the dominant particle size ranges have been reported to be well suited for drug delivery and encapsulation purposes [ 103 ]. No apparent concentration-dependent trend is observed, but the freshly prepared formulations exhibited similar behavior.…”
Section: Resultsmentioning
confidence: 99%
“…also used dopamine-composite chitosan and PAM to prepare hydrogels, which reached swelling equilibrium at 5 ​h, with mass swelling rates of 15.8 [ 58 ]. From another point of view, this also showed that the hydrogel formed by C-CS also enhanced the swelling performance of the DN hydrogel, which can make the DN hydrogel used as a wound dressing to absorb the exudate from the wound site [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Odelius et al showed that the degradation rate of porous structures decreased with decreasing pore size [78]. Thirdly, the weight loss in Sample 3 resulted from the Ps releasing because hydrolytic degradation accelerates the Ps release with weight loss [74]. Still, this weight loss percentage was not more significant than Sample 1's weight loss percentage due to highly absorbent properties of SA polymers.…”
Section: Swelling and Degradation Testsmentioning
confidence: 99%
“…Oliveira et al observed that Ps causes less space for water uptake by filling the pores, thereby reducing the stretching in the fibers with less water [57]. Candido et al also showed that the addition of Ps and the interaction of SA chains with Ps result in low water absorption [74]. The swelling ratio is also correlated with the lower hydrophilic properties of Ps compared to alginate and in this case, practically, only SA adsorbed water leading to swelling and mass gain, at least for a while.…”
Section: Swelling and Degradation Testsmentioning
confidence: 99%